Endoscopic laser therapy for stage III and IV esophageal cancer - Paisal Pongchairerks (2018)
Patients with esophageal cancer frequently present with advanced-stage disease. Many surgeons have adopted a policy of recommending esophagectomy to all patients who are fit enough to withstand major surgery, even if it provides no survival benefit. Only those patients who are too ill are referred for endoscopic laser therapy (ELT) or merely gastrostomy. In this study we investigated the short- and long-term results of esophagectomy and ELT in patients with Stages III and IV squamous cell carcinoma of the thoracic esophagus between January 1989 and April 1993. Thirty-three patients (12 at Stage 111 and 21 at Stage IV) underwent esophagectomy, while 22 patients (4 at Stage III and 18 at Stage IV) had ELT during the same period. Concurrent diseases were more prevalent in the ELT group. In the esophagectomy group, mortality was 19% and 16.7% in patients with Stage III and IV disease, respectively. Major complications were respiratory problems and leakage. Patients who developed major complications stayed an average of almost 100 days in hospital and succumbed shortly after discharge. Patients given ELT had a high mortality due to their severe pre-treatment status. However, those who survived the initial treatment stayed only a few days in hospital with a median survival of 159.5 days. The survival of patients in the two groups did not differ. ELT had the benefit of providing a shorter and cheaper hospital stay even in very advanced cases. It remains to be determined whether ELT patients would have had a final outcome comparable to that of patients offered resection if they had been treated at an earlier stage.